Messengers from the Invisible World among the Inuit of the Eastern Arctic - Frédéric Laugrand (Recherches amérindiennes au Québec, 2018)
The relationships that Inuit maintain with qupirruit (small critters) and the knowledge they have about them remain unknown. In the few available studies that can be found, the emphasis has been mainly on the fears and terror that these little animals bring to humans. Their role in the shamanic initiations has also been emphasized, these small critters being in contact with death and able to revive or to metamorphose. Using classical and contemporary oral sources, this paper addresses a very different aspect of small critters, their role as messengers. Qupirruit are entities able to guide humans in their gestures and their decision-making. They can sometimes accompany them and protect them, or announce events to come. While shamanic traditions are now underground, it is necessary to wonder whether these little critters are not perceived more positively than before, notwithstanding their ambivalence. Les rapports que les Inuits entretiennent avec les qupirruit (les petites bestioles) et les savoirs qu’ils possèdent à leur égard demeurent méconnus. Dans les rares études disponibles, l’accent a surtout été placé sur les peurs et la terreur que suscitent ces petites bêtes auprès des humains. On a également souligné leur rôle dans l’initiation chamanique, ces êtres étant en contact avec la mort et susceptibles de revivre ou de se métamorphoser. À partir de sources orales anciennes et contemporaines, cet article aborde un tout autre aspect des petites bestioles, en particulier leur rôle de messagers. Les qupirruit sont des entités capables de guider les humains dans leurs gestes et leurs prises de décision, de les accompagner et de les protéger, d’annoncer des événements à venir. Alors que les traditions chamaniques ont basculé dans l’invisible, il convient de se demander si les petites bestioles ne sont pas aujourd’hui perçues plus positivement que jadis, nonobstant leur ambivalence. Las relaciones que los Inuit mantienen con los qupirruit (las pequeñas criaturas) y el conocimiento que tienen sobre ellos siguen ...